Compensation for the Wrongfully Convicted: A Pressing Need for Statutory Arrangements in Nepal - Acharya, Jiwan Kumar; Regmi, Rasmi; Bista, Sandhya (Kathmandu School of Law Review, 2021)
Wrongful conviction appears as a form of a miscarriage of justice. Various factors might be responsible for the wrongful conviction of innocent individuals. However, irrespective of the cause, the aftermath of exoneration upon them is beyond imagination. Though they are released after acquittal, an absence of any compensatory provision for the wrongfully convicted appears to be similar to that of incarceration. Taking these concerns into account, the paper in its first part attempts to briefly overview the underlying causes behind wrongful convictions from an individualistic and systemic approach. Presenting some inherent impacts upon the innocent victims through this form of a miscarriage of justice, it justifies rationales for compensatory awards for the victims, emphasizing state obligation. In its second part, the paper attempts to overview the situation of wrongful conviction in Nepal, observing some landmark cases as well as orders made therein by the Supreme Court regarding the state liability upon the victims and orders for the statutory arrangements to address the compensatory claims. This paper justifies the urgency of enacting dedicated legislations for compensation in a wrongful conviction, observing the unavailability of other avenues to obtain compensatory damages at present. It also proposes some considerations to be taken into account while framing such legislation. In dealing with these considerations, this paper proposes a dedicated, independent, external and accessible mechanism to approach compensatory claims by the victims and assessment and award of amounts of damages for them. Examining possible avenues for fund arrangements to award such compensatory claims, the paper finally proposes a separate fund to arrange resources for such compensatory damages to the victims.